Composite shape memory epoxy polymer as well as preparation method and application thereof
By preparing composite shape memory epoxy polymers, the problems of poor activation temperature of existing leak plugging materials in high-temperature deep wells and lack of bonding performance between materials are solved, and efficient leak plugging effect and low leakage loss are achieved.
Patent Information
- Application Number
- CN202311079644.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-25
AI Technical Summary
In the high-temperature deep well leakage plugging operation, the activation temperature is low or high, resulting in poor leakage plugging effect and lack of bonding performance between the materials, resulting in large leakage loss.
The composite shape memory epoxy polymer is adopted. The preparation method includes mixing the aqueous epoxy resin emulsion with different curing agent systems and heating to cure it to form a low-activation high viscosity-high activation high strength-low activation high viscosity composite layer, through high temperature thermal pressure Form shape memory sheets.
Achieve shape memory effect with high activation temperature, strength and toughness. It can expand by 62% after activation above 130℃, adaptively plug the leak space, match different particle sizes to plug the leak particles and strengthen the sealing effect, and high temperature of 150℃ at low concentration The compressive strength reaches more than 12.6MPa, and the leakage loss is less than 50mL.
Smart Images

Figure BDA0004413864730000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of drilling fluids, and in particular relates to a composite shape memory epoxy polymer and a preparation method and application thereof. Background Art
[0002] As oil drilling projects continue to develop into deep wells and complex formations, the problem of well leakage has become increasingly prominent. The leakage channel in complex formations has multi-scale characteristics. Conventional bridging materials are used for plugging. Due to the poor adaptability of the materials used, it is difficult to match the particle size of the optimized material with the size of the leakage channel, resulting in a low plugging success rate.
[0003] Temperature-triggered shape memory materials have the advantages of large recoverable deformation, high strength and fast response speed, which give the plugging technology "intelligent" characteristics. This type of material can produce expansion deformation at a certain temperature (above room temperature) to plug leaks. This type of material can be compressed and fixed at a certain temperature, and stored at room temperature to preserve the deformation. When the temperature is raised to the activation temperature, it will expand and recover its shape, successfully bridge and plug the cracks. It has good adaptability to the size of the cracks, and it is easy to achieve a good bridging and plugging effect in coordination with other materials.
[0004] Chinese patent CN113122204A discloses a memory polymer type temperature-controlled rigid expansion plugging agent, which is prepared by mixing oligomer monomers, cross-linking agents and catalysts and injecting them into a mold, undergoing cross-linking reaction, cooling and demoulding, and then granulating to obtain a temperature-controlled rigid expansion plugging agent. Its activation temperature is 70°C to 100°C. After reaching the activation temperature, it can plug cracks of different openings, with a pressure bearing capacity of ≥8MPa and a small leakage volume. However, the activation temperature of the plugging agent is lower than 100°C, and the expansion parameters are not disclosed.
[0005] Chinese patent CN113652212B discloses a shape memory leak prevention and plugging system. The memory plugging agent composition contains epoxy resin, amine curing agent, active diluent and foaming agent. The intelligent plugging system based on shape memory material enables the plugging fluid to identify the temperature of the leaking layer, realizes shape change through the shape recovery of the shape memory plugging agent, and develops a thermal shape memory intelligent leak prevention and plugging material to form an intelligent leak prevention and plugging technology. The shape memory polymer has a response temperature range of 80-105°C and a volume expansion rate of 120%. However, the activation temperature of the memory plugging agent composition is basically lower than 100°C, and is not suitable for 100-120°C.
[0006] Chinese patent CN114702722B discloses a high-temperature shape memory foam composite material, which is a mixture of a water dispersion of nanoparticles and an epoxy monomer to obtain a Pickering emulsion; a curing agent is added to the Pickering emulsion and then poured into a mold, and the shape memory epoxy foam composite material is cured by heating. The rubber state storage modulus of the shape memory epoxy foam composite material is 10MPa; when the shape memory transition temperature is 100°C, the expansion rate is 350%; when the shape memory transition temperature is 170°C, the expansion rate is 50%, and the crack blocking pressure is 20MPa. However, although the activation temperature of the composite material is higher than 100°C, the materials lack bonding properties, and the plugging system relies on particle size grading for plugging, so the leakage of the high-concentration plugging system implemented is large.
[0007] Some of the existing shape memory plugging products have an activation temperature of less than 100°C. When used in high-temperature deep well plugging operations, they may expand prematurely before entering the leaking layer space, and lose the effect of adaptive leakage size; some of them are used as water-based drilling fluid plugging materials in the form of sheets or particles, but their hydrophilicity is poor, affecting their dispersion in the water-based drilling fluid; and some of them use materials of different particle sizes to bridge and fill under pressure through grading. Some flexible materials can play a "reinforcement winding" role, but the various materials cannot interact with each other and adhere tightly together, resulting in the inability to efficiently plug cracks and reduce repeated leakage due to changes in downhole pressure.
[0008] Therefore, there is an urgent need for a shape memory plugging material with high activation temperature, good toughness and simple shaping process for fractured leakage, where the temperature of the formation is high, the leakage space is complex and multi-scale, and the plugging particle size is difficult to match. Summary of the invention
[0009] In order to solve the above problems in the prior art, the present invention provides a composite shape memory epoxy polymer and a preparation method and application thereof.
[0010] In a first aspect, the present invention provides a method for preparing a composite shape memory epoxy polymer, characterized in that the preparation method comprises the following steps:
[0011] S1: uniformly mixing the waterborne epoxy resin emulsion and the curing agent system A, and heating and curing to obtain a first cured product;
[0012] S2: Evenly mix the waterborne epoxy resin emulsion and the curing agent system B, and heat and cure to obtain a second cured product;
[0013] S3: Mixing the first solidified body and the second solidified body to obtain a composite shape memory epoxy polymer.
[0014] As a specific embodiment of the present invention, the water-based epoxy resin includes at least one of epoxy resin E51, GEM254, epoxy resin GEM370, and polypropylene glycol diglycidyl ether PPGGE.
[0015] As a specific embodiment of the present invention, the curing agent system A includes at least one of a monoamine curing agent, a polyamine curing agent, and a polyphenol compound; preferably selected from at least one of diglycolamine (DGA), tetravinylpentamine-TETA, D230, D400, tannic acid, catechol and dopamine; more preferably, the curing agent system A is a mixture of diglycolamine-DGA and tetravinylpentamine-TETA, wherein the mass ratio of diglycolamine-DGA to tetravinylpentamine-TETA is (3-8):1.
[0016] As a specific embodiment of the present invention, the mass of the curing agent system A is 30-50% of the mass of the waterborne epoxy resin.
[0017] As a specific embodiment of the present invention, the curing agent system A also includes binary polyether epoxy, and the binary polyether epoxy is preferably polypropylene glycol diglycidyl ether (PPGGE). The addition amount of the binary polyether epoxy is 5-10% of the mass of the waterborne epoxy resin.
[0018] As a specific embodiment of the present invention, in step S1, the heating and curing conditions include: a curing temperature of 60-120°C and a curing time of 2-6h; preferably, the heating and curing is a step-by-step temperature curing, including curing at 60-80°C for 4h and curing at 100-120°C for 2h, wherein the glass transition temperature measured by a differential calorimeter is 60-80°C.
[0019] As a specific embodiment of the present invention, the present invention adopts a step-by-step curing temperature rise mode, which can obtain a material with better toughness than a single curing mode at a certain temperature for a period of time.
[0020] As a specific embodiment of the present invention, the curing agent system B includes at least one of an aromatic amine curing agent and a polyamine curing agent, preferably selected from at least one of diethyltoluenediamine-DETDA, diaminodiphenyl sulfone-DDS, diaminodiphenylmethane-DDM, tetravinylpentamine-TETA, and polyetheramine D230; more preferably, the curing agent system B is a mixture of diaminodiphenyl sulfone-DDS and tetravinylpentamine-TETA; wherein the mass ratio of diaminodiphenyl sulfone-DDS to tetravinylpentamine-TETA is (1 to 5):1.
[0021] As a specific embodiment of the present invention, the mass of the curing agent system B is 60-80% of the mass of the waterborne epoxy resin.
[0022] As a specific embodiment of the present invention, in step S2, the heating and curing conditions include: a heating temperature of 60-140°C and a curing time of 2-12h; preferably, the heating and curing is a step-by-step temperature curing, including curing at 60-80°C for 3-5h, curing at 100-120°C for 1-3h, and curing at 120-140°C for 2-4h, wherein the glass transition temperature measured by a differential calorimeter is 100-130°C.
[0023] As a specific embodiment of the present invention, in step S3, the mass ratio of the first solidified body to the second solidified body is (1-2): 1;
[0024] The mixing method of the first solidified body and the second solidified body includes hot pressing and sheeting;
[0025] Wherein, the conditions for hot pressing the first solidified body and the second solidified body in a ratio of 1:1 include: temperature of 120-160°C and pressure of 8-10Mpa;
[0026] The conditions for hot pressing the first solidified body and the second solidified body in a ratio of 2:1 include: a temperature of 120-160° C. and a pressure of 8-12 MPa.
[0027] As a preferred embodiment of the present invention, the first solidified body and the second solidified body are hot pressed in a ratio of 2:1, and the hot pressing mode is that the first solidified body is superimposed on the second solidified body and then on the first solidified body, wherein the second solidified body is located in the middle layer, and the solidified body is gradually flattened during the hot pressing process; the thin sheet material obtained by hot pressing is used as a plugging agent. The thin sheet plugging agent has stronger retention than the spherical one, so it is pressed into a thin sheet, and preferably, the thickness of the sheet is 0.5-1mm.
[0028] In a second aspect, the present invention provides a composite shape memory epoxy polymer obtained by the preparation method described in the first aspect, wherein the expansion rate of the composite shape memory epoxy polymer is 40-70%.
[0029] In a third aspect, the present invention provides the use of the composite shape memory epoxy polymer obtained by the preparation method described in the first aspect or the composite shape memory epoxy polymer described in the second aspect in the field of plugging agents;
[0030] As a specific embodiment of the present invention, the composite shape memory epoxy polymer is crushed and combined with a plugging material to serve as a plugging agent for crack plugging.
[0031] As a specific embodiment of the present invention, the composite shape memory epoxy polymer is crushed into particles of different sizes between 6-100 meshes.
[0032] The above raw materials in the present invention can be prepared in-house or commercially available, and the present invention is not particularly limited thereto.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The composite shape memory epoxy polymer of the present invention first uses water-based epoxy emulsion to prepare epoxy resins with high and low glass transition temperatures, and then forms a low-activation high-viscosity-high-activation high-strength-low-activation high-viscosity composite layer by combining an epoxy polymer layer with a low glass transition temperature, high toughness and high viscosity with an epoxy polymer layer with a high glass transition temperature and high strength, and then forms a shape memory sheet by hot pressing at a high temperature higher than the shape memory activation temperature. After the sheet is cooled to room temperature and the pressure is released, the surface viscous layer solidifies and loses its viscous effect, making it easy to disperse in water-based or oil-based drilling fluids and easy to enter the leakage channel.
[0035] 2. When the drilling fluid reaches the high-temperature and high-pressure leaking formation, the composite shape memory epoxy polymer of the present invention deforms and stores energy and accumulates heat to form recovery power. The outer low-activated viscosity layer first expands to build a bridge in the leaking layer. At the same time, the viscosity gradually recovers under high temperature and high pressure, adsorbing and adhering to other plugging materials in the surrounding area to form a bridging network structure, while the surrounding free plugging particles are filled to quickly reduce the leakage amount. The high-activated and high-strength shape memory plugging material in the middle layer continues to accumulate energy, gradually expands, and releases elasticity, further compacting the plugging layer and improving the pressure bearing strength and "breathing effect" of the plugging layer.
[0036] 3. The composite shape memory epoxy polymer of the present invention has high activation temperature, high strength and high toughness. Its shape memory activation temperature is above 130°C. When used as a plugging material, it can expand by 62% after reaching the activation temperature, adapt to the plugging space, match other particle size plugging particles and bond other plugging material particles at the same time, strengthen the plugging effect, and when added in low concentration, the high temperature 150°C pressure bearing strength reaches more than 12.6MPa, and the leakage volume is less than 50mL, achieving the effect of effective bridging pressure bearing, sealing and plugging, and expanding the safe density window. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.
[0038] The test methods used in the embodiments of the present invention include:
[0039] 1. Activation phase change temperature Tg test method:
[0040] The phase transition temperature Tg of the prepared thin film was analyzed using a Q100 differential scanning calorimeter. In a nitrogen environment, the temperature was first increased from room temperature to 300°C at 10°C / min, then decreased from 300°C to -30°C at 10°C / min to eliminate the thermal history, and then increased from -30°C to 300°C at 10°C / min to analyze the glass transition temperature of the sample.
[0041] 2. Expansion rate test method
[0042] The pressed sheet (thickness H0) is reheated to its Tg temperature, its thickness H1 is measured, and the expansion ratio is calculated:
[0043]
[0044] 3. Plugging performance test method
[0045] A new long crack plugging test device was used to simulate the high temperature and high pressure conditions in the well to evaluate the crack plugging pressure bearing capacity of the plugging material. The crack opening was 3×2mm, and the plugging pressure bearing capacity of the plugging material was evaluated at room temperature of 25℃ and 100-180℃.
[0046] Example 1
[0047] This embodiment provides a composite shape memory epoxy polymer and a preparation method thereof, the specific details of which are as follows:
[0048] S1: 100 g of waterborne epoxy resin emulsion E51, curing agent diglycolamine-DGA (25% of the epoxy resin mass) and tetraethylenepentamine-TETA (10% of the epoxy resin mass) were mixed and stirred evenly, poured onto the surface of the substrate, heated to 80° C. in an oven for curing for 4 h and 120° C. for curing for 2 h to obtain a first cured body. The glass transition temperature Tg1 of the first cured body measured by DSC was 60° C.;
[0049] S2: 100 g of waterborne epoxy resin emulsion E51, curing agent diethyltoluenediamine-DETDA (40% of the epoxy resin mass) and polyetheramine D230 (20% of the epoxy resin mass) were mixed and stirred evenly, poured onto the surface of the substrate, heated to 60° C. in an oven for curing for 4 h, 100° C. for curing for 2 h, and 120° C. for curing for 2 h to obtain a second cured body. The glass transition temperature Tg2 of the second cured body measured by DSC was 100° C.;
[0050] S3: stacking the first solidified body and the second solidified body in the order of first solidified body + second solidified body + first solidified body, hot pressing them into sheets at a temperature of 120° C. and 8 MPa, and cooling them to room temperature while maintaining the pressure to obtain a composite shape memory epoxy polymer sheet with a thickness of 0.5 mm.
[0051] When the composite shape memory epoxy polymer sheet obtained in Example 1 is heated to 100° C., its expansion rate is 50%.
[0052] Application Example 1
[0053] The composite shape memory epoxy polymer flakes prepared in Example 1 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 1:1, and the total concentration was 4%; combined with 8% calcium carbonate particles (20-40 mesh) and 0.2% cottonseed shells (2-3mm), added to 4% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 120°C, and the above experimental plugging slurry was added to test the plugging performance of the composite shape memory epoxy polymer obtained in Example 1. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Example 1 has a pressure bearing capacity of 7MPa and a leakage volume of 45mL.
[0054] Comparative application example 1
[0055] 8% calcium carbonate particles (20-40 mesh) and 0.2% cottonseed hulls (2-3mm) were combined and added to 4% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 120°C, and the experimental result was total leakage.
[0056] Example 2
[0057] This embodiment provides a composite shape memory epoxy polymer and a preparation method thereof, the specific details of which are as follows:
[0058] S1: 100 g of water-based epoxy resin emulsion E51, curing agents including diglycolamine - DGA (25% of the mass of epoxy resin) and tetravinylpentamine - TETA (5% of the mass of epoxy resin), and epoxy monomer polypropylene glycol diglycidyl ether - PPGGE (10% of the mass of epoxy resin) were mixed and stirred evenly, poured onto the surface of the substrate, and cured in an oven at 60°C for 4 h and at 100°C for 2 h to obtain a first cured body. The glass transition temperature Tg1 of the first cured body was measured to be 80°C.
[0059] S2: 100 g of waterborne epoxy resin emulsion E51, diaminodiphenyl sulfone-DDS (60% of the epoxy resin mass) and tetravinylpentamine-TETA (20% of the epoxy resin mass) were mixed and stirred evenly, poured onto the surface of the substrate, heated to 80° C. in an oven for curing for 4 h, 120° C. for curing for 2 h, and 140° C. for curing for 2 h to obtain a second cured body, and the glass transition temperature Tg2 of the second cured body was measured to be 130° C.;
[0060] S3: stack the first solidified body obtained in step S1 and the second solidified body obtained in step S2 in the order of first solidified body + second solidified body + first solidified body, hot press at 160° C. and 10 MPa, maintain the pressure and cool to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0061] The composite shape memory epoxy polymer sheet obtained in Example 2 was heated to 150° C. and its expansion rate was 62%.
[0062] Application Example 2
[0063] The composite shape memory epoxy polymer flakes obtained in Example 2 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 3:2, and the total concentration was 5%; combined with 12% calcium carbonate particles (5% (20-40 mesh) + 7% (100-800 mesh) and 0.4% cottonseed shells (2-3mm), added to 4% bentonite base slurry to form an experimental plugging slurry; a 3×2mm long crack was used for the plugging experimental device test, and the plugging performance of the composite shape memory epoxy polymer obtained in Example 2 was tested at 150°C by adding the above-mentioned experimental plugging slurry. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Example 2 has a pressure bearing capacity of 12.6MPa and a leakage volume of 10mL.
[0064] Comparative Application Example 2
[0065] 12% calcium carbonate particles (5% (20-40 mesh) + 7% calcium carbonate (100-800 mesh) and 0.4% cottonseed hull (2-3mm) were combined and added to 4% bentonite base slurry to form an experimental plugging slurry; a 3×2mm long crack was used for plugging experimental device testing, and the above experimental plugging slurry was added at 150°C. The experimental result was total leakage.
[0066] Example 3
[0067] S1: As in Example 1, except that the curing agents used to prepare the cured body 1 are diglycolamine-DGA (25% of the mass of the epoxy resin) and D230 (25% of the mass of the epoxy resin), and the mixture is cured in an oven at 70°C for 4 hours and at 100°C for 2 hours to obtain a first cured body. The glass transition temperature Tg1 of the first cured body is measured to be 73°C.
[0068] S2: diaminodiphenylmethane-DDM (60% of the epoxy resin mass) and tetravinylpentamine-TETA (20% of the epoxy resin mass), cured at 80°C for 4h, 120°C for 2h, and 140°C for 2h to obtain a second cured body, and the glass transition temperature Tg2 of the second cured body was measured to be 115°C;
[0069] S3: stacking the first solidified body + the second solidified body + the first solidified body in the order of each other, hot pressing at a temperature of 140° C. and 10 MPa, maintaining the pressure and cooling to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0070] The composite shape memory epoxy polymer sheet obtained in Example 3 was heated to 115° C., and its expansion rate was 43%.
[0071] Application Example 3
[0072] The composite shape memory epoxy polymer flakes obtained in Example 3 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 3:2, with a total concentration of 5%; combined with 10% calcium carbonate particles (5% (20-40 mesh) + 5% (100-800 mesh) and 0.4% polyester fiber 2-3mm), added to 4% bentonite base slurry, and tested at 150°C using a long crack (3×2mm) plugging experimental device, and the plugging performance of the system before and after the addition of the memory epoxy flake plugging agent. The plugging system formed by Example 3 has a pressure bearing capacity of 9.3MPa and a leakage volume of 15mL.
[0073] Comparative Application Example 3
[0074] 5% calcium carbonate (20-40 mesh) + 5% calcium carbonate (100-800 mesh) was combined with 0.4% polyester fiber (2-3mm), added to 4% bentonite base slurry to form an experimental plugging slurry. The long crack (3×2mm) plugging experimental device was used to test 150°C. When the above plugging slurry was added, the experimental result was total leakage.
[0075] Example 4
[0076] S1: 100 g of waterborne epoxy resin emulsion E51, curing agents such as diglycolamine-DGA (30% of the mass of epoxy resin) and D400 (20% of the mass of epoxy resin), and epoxy monomer polypropylene glycol diglycidyl ether-PPGGE (10% of the mass of epoxy resin) are mixed and stirred evenly, poured onto the surface of the substrate, and cured in an oven at 60°C for 4 hours and at 100°C for 2 hours to obtain a first cured body. The glass transition temperature Tg1 of the first cured body is measured to be 60°C.
[0077] S2: 100 g of waterborne epoxy resin emulsion E51, curing agent diaminodiphenylmethane-DDM (50% of the epoxy resin mass) and D230 (20% of the epoxy resin mass) were mixed and stirred evenly, poured onto the surface of the substrate, heated to 80° C. in an oven for curing for 4 h, 120° C. for curing for 2 h, and 140° C. for curing for 2 h to obtain a second cured body, and the glass transition temperature Tg2 of the second cured body was measured to be 106° C.;
[0078] S3: stacking the first solidified body and the second solidified body in the order of first solidified body + second solidified body + first solidified body, hot pressing at a temperature of 130° C. and 10 MPa, maintaining the pressure and cooling to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0079] When the composite shape memory epoxy polymer sheet obtained in Example 4 is heated to 110° C., its expansion rate is 46%.
[0080] Application Example 4
[0081] The composite shape memory epoxy polymer flakes obtained in Example 4 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 3:2, and the total concentration was 5%; combined with 12% calcium carbonate particles (5% (20-40 mesh) + 7% (100-800 mesh) and 0.4% polyester fiber (2-3mm), added to 4% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 150°C, and the above-mentioned experimental plugging slurry was added to test the plugging performance of the composite shape memory epoxy polymer obtained in Example 4. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Example 4 has a pressure bearing capacity of 8.9MPa and a leakage volume of 13mL.
[0082] Comparative Application Example 4
[0083] 5% calcium carbonate (3% (10-20 mesh) and 2% (30-50 mesh)) + 7% calcium carbonate (100-800 mesh) was combined with 0.4% polyester fiber (2-3mm), added to 4% bentonite base slurry, and tested at 150°C using a long crack (3×2mm) plugging experimental device. The above experimental plugging slurry was added, and the experimental result was total loss.
[0084] Example 5
[0085] S1: According to 100g of water-based epoxy resin emulsion E51, the curing agent is diglycolamine-DGA (20% of the mass of the epoxy resin) and tannic acid (30% of the mass of the epoxy resin), and the curing is carried out at 60°C for 4h and 100°C for 2h in an oven to obtain a first cured body. The glass transition temperature Tg1 of the first cured body is measured to be 76°C.
[0086] S2: According to 100g of waterborne epoxy resin emulsion E51, curing agent is diaminodiphenylmethane-DDM (50% of the epoxy resin mass) and polyetheramine D230 (20% of the epoxy resin mass), curing at 80°C for 4h, 110°C for 2h, and 130°C for 2h to obtain a second cured body, and the glass transition temperature Tg2 of the second cured body is measured to be 106°C;
[0087] S3: stacking the first solidified body and the second solidified body in the order of first solidified body + second solidified body + first solidified body, hot pressing at a temperature of 130° C. and 10 MPa, maintaining the pressure and cooling to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0088] The composite shape memory epoxy polymer sheet obtained in Example 5 was heated to 106° C., and its expansion rate was 45%.
[0089] Application Example 5
[0090] The composite shape memory epoxy polymer flakes obtained in Example 5 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 3:2, and the total concentration was 5%; combined with 10% calcium carbonate particles (5% (20-40 mesh) + 5% (100-800 mesh) and 0.4% polyester fiber (2-3mm), added to 4% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 150°C, and the above-mentioned experimental plugging slurry was added to test the plugging performance of the composite shape memory epoxy polymer obtained in Example 5. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Example 5 has a pressure bearing capacity of 7.9MPa and a leakage volume of 15mL.
[0091] Comparative Application Example 5
[0092] 5% calcium carbonate (3% (10-20 mesh) and 2% (30-50 mesh)) + 5% calcium carbonate (2% (20-40 mesh) + 3% (100-800 mesh)) was combined with 0.4% polyester fiber (2-3mm), and added to 4% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 150°C, and the above experimental plugging slurry was added, and the experimental result was total loss.
[0093] Example 6
[0094] S1: According to 100g of water-based epoxy resin emulsion E51, the curing agent is diglycolamine-DGA (30% of the mass of the epoxy resin) and catechol (20% of the mass of the epoxy resin), and the curing is carried out at 60°C for 4h and 100°C for 2h to obtain a first cured body. The glass transition temperature Tg1 of the first cured body is measured to be 63°C.
[0095] S2: According to 100g of waterborne epoxy resin emulsion E51, curing agent is diaminodiphenylmethane-DDM (70% of the epoxy resin mass) and D230 (10% of the epoxy resin mass), curing at 80°C for 4h, 120°C for 2h, and 140°C for 2h to obtain a second cured body, and the glass transition temperature Tg2 of the second cured body is measured to be 121°C;
[0096] S3: stacking the first solidified body and the second solidified body in the order of first solidified body + second solidified body + first solidified body, hot pressing at a temperature of 150° C. and 10 MPa, maintaining the pressure and cooling to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0097] When the composite shape memory epoxy polymer sheet obtained in Example 6 is heated to 121° C., its expansion ratio is 40%.
[0098] Application Example 6
[0099] The composite shape memory epoxy polymer flakes obtained in Example 6 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 3:2, and the total concentration was 5%; combined with 10% calcium carbonate particles (5% (20-40 mesh) + 5% (100-800 mesh) and 0.4% walnut shells (2-3mm), added to 4% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 150°C, and the above-mentioned experimental plugging slurry was added to test the plugging performance of the composite shape memory epoxy polymer obtained in Example 6. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Example 6 has a pressure bearing capacity of 8.3MPa and a leakage volume of 15mL.
[0100] Comparative Application Example 6
[0101] 5% calcium carbonate (3% (10-20 mesh) and 2% (30-50 mesh)) + 5% calcium carbonate (2% (20-40 mesh) + 3% (100-800 mesh)) was combined with 0.4% walnut shell (2-3mm), and added to 6% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 150°C, and the above experimental plugging slurry was added, and the experimental result was total loss.
[0102] Example 7
[0103] S1: 100g of waterborne epoxy resin emulsion E51, curing agent diglycolamine-DGA (20% of the mass of epoxy resin) and dopamine (30% of the mass of epoxy resin) were mixed and stirred evenly, poured onto the surface of the substrate, and cured in an oven at 60°C for 4h and 100°C for 2h to obtain a first cured body. The glass transition temperature Tg1 of the first cured body was measured to be 72°C.
[0104] S2: 100 g of waterborne epoxy resin emulsion E51, curing agent diaminodiphenylmethane-DDM (40% of the epoxy resin mass) and TETA (30% of the epoxy resin mass) were mixed and stirred evenly, poured onto the surface of the substrate, heated to 80° C. in an oven for curing for 4 h, 110° C. for curing for 2 h, and 130° C. for curing for 2 h to obtain a second cured body. The glass transition temperature Tg2 of the second cured body measured by DSC was 101° C.;
[0105] S3: stacking the first solidified body and the second solidified body in the order of first solidified body + second solidified body + first solidified body, hot pressing at a temperature of 130° C. and 10 MPa, maintaining the pressure and cooling to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0106] The composite shape memory epoxy polymer sheet obtained in Example 7 was heated to 101° C., and its expansion rate was 44%.
[0107] Application Example 7
[0108] The composite shape memory epoxy polymer flakes obtained in Example 7 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 3:2, and the total concentration was 5%; combined with 10% calcium carbonate particles (5% (20-40 mesh) + 5% (100-800 mesh) and 0.4% walnut shells (2-3mm), added to 4% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 150°C, and the above-mentioned experimental plugging slurry was added to test the plugging performance of the composite shape memory epoxy polymer obtained in Example 7. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Example 7 has a pressure bearing capacity of 7.1MPa and a leakage volume of 35mL.
[0109] Comparative Application Example 7
[0110] 5% calcium carbonate (3% (10-20 mesh) and 2% (30-50 mesh)) + 5% calcium carbonate (2% (20-40 mesh) + 3% (100-800 mesh)) was combined with 0.4% walnut shell (2-3mm), and added to 10% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 150°C, and the above experimental plugging slurry was added, and the experimental result was total loss.
[0111] Example 8
[0112] S1: According to 100g of waterborne epoxy resin emulsion E51, curing agents are diglycolamine-DGA (20% of the mass of epoxy resin), dopamine (20% of the mass of epoxy resin) and D230 (10% of the mass of epoxy resin), curing at 60°C for 4h and 100°C for 2h to obtain a first cured body, and the glass transition temperature Tg1 of the first cured body is measured to be 70°C;
[0113] S2: According to 100g of waterborne epoxy resin emulsion E51, curing agent is diaminodiphenylmethane-DDM (70% of the epoxy resin mass) and D400 (10% of the epoxy resin mass), curing at 80°C for 4h, 120°C for 2h, and 140°C for 2h to obtain a second cured body, and the glass transition temperature Tg2 of the second cured body is measured to be 105°C;
[0114] S3: stack the first solidified body obtained in step S1 and the second solidified body obtained in step S2 in the order of first solidified body + second solidified body + first solidified body, hot press at 130° C. and 10 MPa, maintain the pressure and cool to room temperature to obtain a 1 mm thick composite shape memory epoxy polymer sheet.
[0115] The composite shape memory epoxy polymer sheet obtained in Example 8 was heated to 105° C., and its expansion rate was 48%.
[0116] Application Example 8
[0117] The composite shape memory epoxy polymer flakes obtained in Example 8 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 3:2, and the total concentration was 5%; combined with 10% calcium carbonate particles (5% (20-40 mesh) + 5% (100-800 mesh) and 0.4% elastic mesh (2-3mm), added to 4% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 150°C, and the plugging performance of the composite shape memory epoxy polymer obtained in Example 8 was tested by adding the above-mentioned experimental plugging slurry. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Example 8 has a pressure bearing capacity of 10.1MPa and a leakage volume of 30mL.
[0118] Comparative Application Example 8
[0119] 5% calcium carbonate (3% (7-20 mesh) and 2% (30-50 mesh)) + 5% calcium carbonate (2% (20-40 mesh) + 3% (100-800 mesh)) was combined with 0.4% elastic mesh (2-3mm), and added to 6% bentonite base slurry to form an experimental plugging slurry; a long crack (3×2mm) plugging experimental device was used to test 150°C, and the above experimental plugging slurry was added, and the experimental result was total loss.
[0120] Example 9
[0121] S1: 100 g of waterborne epoxy resin emulsion E51, curing agent diglycolamine-DGA (20% of the epoxy resin mass), tannic acid (20% of the epoxy resin mass) and TETA (10% of the epoxy resin mass) were mixed and stirred evenly, poured onto the surface of the substrate, and cured in an oven at 60° C. for 4 h and 100° C. for 2 h to obtain a first cured body. The glass transition temperature Tg1 of the first cured body was measured to be 69° C.;
[0122] S2: 100 g of waterborne epoxy resin emulsion E51, curing agent diaminodiphenylmethane-DDM (60% of the epoxy resin mass) and D230 (20% of the epoxy resin mass) were mixed and stirred evenly, poured onto the surface of the substrate, heated to 80° C. in an oven for curing for 4 h, 120° C. for curing for 2 h, and 130° C. for curing for 2 h to obtain a second cured body, and the glass transition temperature Tg2 of the second cured body was measured to be 122° C.;
[0123] S3: stack the first solidified body obtained in step S1 and the second solidified body obtained in step S2 in the order of first solidified body + second solidified body + first solidified body, hot press at 150° C. and 10 MPa, maintain the pressure and cool to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0124] The composite shape memory epoxy polymer sheet obtained in Example 9 was heated to 101° C., and its expansion ratio was 46%.
[0125] Application Example 9
[0126] The composite shape memory epoxy polymer flakes obtained in Example 9 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 3:2, and the total concentration was 5%; combined with 10% calcium carbonate particles (5% (20-40 mesh) + 5% (100-800 mesh) and 0.4% elastic mesh (2-3mm), and added to 4% bentonite base slurry to form an experimental plugging slurry; a 3×2mm long crack was used for the plugging experimental device test, and the plugging performance of the composite shape memory epoxy polymer obtained in Example 9 was tested at 150°C by adding the above-mentioned experimental plugging slurry. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Example 9 has a pressure bearing capacity of 11.8MPa and a leakage volume of 15mL.
[0127] Comparative Application Example 9
[0128] 5% calcium carbonate (2% (7-10 mesh) + 1% (10-20 mesh) + 2% (30-50 mesh)) + 5% calcium carbonate (2% (20-40 mesh) + 3% (100-800 mesh)) was combined with 0.4% elastic mesh (2-3mm), and added into 4% bentonite base slurry to form an experimental plugging slurry; a 3×2mm long crack was used for plugging experimental device testing, and the above experimental plugging slurry was added at 150°C, and the experimental result was total loss.
[0129] Example 10
[0130] S1: According to 100g of water-based epoxy resin emulsion E51, the curing agent is diglycolamine-DGA (20% of the mass of epoxy resin), catechol (20% of the mass of epoxy resin) and TETA (10% of the mass of epoxy resin), and the mixture is cured at 60°C for 4h and at 100°C for 2h to obtain a first cured body. The glass transition temperature Tg1 of the first cured body is measured to be 65°C.
[0131] S2: According to 100g of waterborne epoxy resin emulsion E51, curing agent is diaminodiphenylmethane-DDM (60% of the epoxy resin mass) and D230 (10% of the epoxy resin mass), curing at 80°C for 4h, 110°C for 2h, and 130°C for 2h to obtain a second cured body, and the glass transition temperature Tg2 of the second cured body is measured to be 110°C;
[0132] S3: stack the first solidified body obtained in step S1 and the second solidified body obtained in step S2 in the order of first solidified body + second solidified body + first solidified body, hot press at 130° C. and 10 MPa, maintain the pressure and cool to room temperature to obtain a 1 mm thick composite shape memory epoxy polymer sheet.
[0133] The composite shape memory epoxy polymer sheet obtained in Example 10 was heated to 105° C., and its expansion ratio was 46%.
[0134] Application Example 10
[0135] The composite shape memory epoxy polymer flakes obtained in Example 10 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 3:2, and the total concentration was 5%; combined with 10% calcium carbonate particles (5% (20-40 mesh) + 5% (100-800 mesh) and 0.4% elastic mesh (2-3mm), and added to 4% bentonite base slurry to form an experimental plugging slurry; a 3×2mm long crack was used for the plugging experimental device test, and the plugging performance of the composite shape memory epoxy polymer obtained in Example 10 was tested at 150°C by adding the above-mentioned experimental plugging slurry. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Example 10 has a pressure bearing capacity of 7.8MPa and a leakage volume of 15mL.
[0136] Comparative Application Example 10
[0137] 5% calcium carbonate (3% (7-20 mesh) + 2% (30-50 mesh)) + 8% calcium carbonate (2% (20-40 mesh) + 3% (80-100 mesh) + 3% (100-800 mesh)) was combined with 0.4% elastic mesh (2-3mm), and added into 4% bentonite base slurry to form an experimental plugging slurry; a 3×2mm long crack was used for plugging experimental device testing, and at 150°C, all leakage occurred after the addition of the above experimental plugging slurry.
[0138] Comparative Example 1
[0139] Steps S1 and S2 are the same as in Example 2, but the sheet pressing in step S3 is different. The specific details are as follows:
[0140] S3: stacking the first solidified body and the second solidified body in sequence, hot pressing at a temperature of 160° C. and 10 MPa, maintaining the pressure and cooling to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0141] The composite shape memory epoxy polymer sheet obtained in Comparative Example 1 was heated to 80°C, and its expansion rate was 18%;
[0142] The composite shape memory epoxy polymer flakes obtained in Comparative Example 1 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 4:3, and the total concentration was 7%; combined with 12% calcium carbonate particles (5% (20-40 mesh) + 7% (100-800 mesh) and 0.4% cottonseed shells (2-3mm), added to 4% bentonite base slurry to obtain experimental plugging slurry; tested at 150°C using a long crack (3×2mm) plugging experimental device, and added to the above plugging slurry. The experimental results showed that the plugging system including the composite shape memory epoxy polymer flakes obtained in Comparative Example 1 had a pressure bearing of 6.2MPa and a leakage of 113mL; the plugging agent without memory epoxy flakes was completely lost.
[0143] Comparative Example 2
[0144] Steps S1 and S2 are the same as in Example 2, but the sheet pressing in step S3 is different. The specific details are as follows:
[0145] S3: stacking two sheets of the first solidified body, hot pressing at a temperature of 160° C. and 10 MPa, maintaining the pressure and cooling to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0146] The composite shape memory epoxy polymer sheet obtained in Comparative Example 2 was heated to 130° C., and its expansion rate was 5%.
[0147] The composite shape memory epoxy polymer flakes obtained in Comparative Example 2 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 4:3, and the total concentration was 7%; combined with 12% calcium carbonate particles (5% (20-40 mesh) + 7% (100-800 mesh) and 0.4% cottonseed shells (2-3mm), added to 4% bentonite base slurry to obtain experimental plugging slurry; tested at 150°C using a long crack (3×2mm) plugging experimental device, and added to the above plugging slurry. The experimental results show that the plugging system including the composite shape memory epoxy polymer flakes obtained in Comparative Example 2 has a pressure bearing capacity of 8.7MPa and a leakage loss of 160mL.
[0148] Comparative Example 3
[0149] Steps S1 and S2 are the same as those in Example 2, but step S3 is different. The specific details are as follows:
[0150] S3: stacking two sheets of the second solidified body, hot pressing at a temperature of 160° C. and 10 MPa, maintaining the pressure and cooling to room temperature to obtain a composite shape memory epoxy polymer sheet with a thickness of 1 mm.
[0151] The composite shape memory epoxy polymer sheet obtained in Comparative Example 3 was heated to 140° C., and its expansion rate was 8%.
[0152] The composite shape memory epoxy polymer flakes obtained in Comparative Example 3 were crushed into (10-20 mesh) and (30-50 mesh), mixed in a ratio of 4:3, and the total concentration was 7%; combined with 12% calcium carbonate particles (5% (20-40 mesh) + 7% (100-800 mesh) and 0.4% cottonseed shells (2-3mm), added to 4% bentonite base slurry to obtain experimental plugging slurry; tested at 150°C using a long crack (3×2mm) plugging experimental device, and added to the above plugging slurry. The experimental results showed that the plugging system including the composite shape memory epoxy polymer flakes obtained in Comparative Example 3 had a pressure bearing capacity of 8.2MPa and a leakage loss of 125mL.
[0153] In summary, the composite shape memory epoxy polymer of the present invention first uses water-based epoxy emulsion to prepare epoxy resins with high and low glass transition temperatures, and then forms a low-activation high-viscosity-high-activation high-strength-low-activation high-viscosity composite layer by combining an epoxy polymer layer with a low glass transition temperature, high toughness and high viscosity with an epoxy polymer layer with a high glass transition temperature and high strength, and then forms a shape memory sheet by hot pressing at a high temperature higher than the shape memory activation temperature. After the sheet is cooled to room temperature and the pressure is released, the surface viscous layer solidifies and loses its viscous effect, making it easy to disperse in water-based or oil-based drilling fluids and also easy to enter the leakage channel.
[0154] When the drilling fluid reaches the high-temperature and high-pressure leaking formation, the epoxy resin deforms and stores energy and accumulates heat to form recovery power. The outer low-activated viscosity layer first expands to build bridges in the leaking layer. At the same time, the viscosity gradually recovers under high temperature and high pressure, adsorbing and adhering to other plugging materials around it to form a bridging network structure, while the surrounding free plugging particles are filled to quickly reduce the leakage amount. The high-activated and high-strength shape memory plugging material in the middle layer continues to accumulate energy, gradually expands, and releases elasticity, further compacting the plugging layer and improving the pressure bearing strength and "breathing effect" of the plugging layer.
[0155] Composite shape memory epoxy polymer has high activation temperature, high strength and high toughness. Its shape memory activation temperature is above 130℃. When used as plugging material, it can expand by 62% after reaching the activation temperature, adapt to the plugging space, match other plugging particles with different particle sizes, and bond other plugging material particles to strengthen the plugging effect. When added in low concentration, the high temperature 150℃ pressure bearing strength reaches more than 12.6MPa, and the leakage volume is less than 50mL, achieving the effect of effective bridging pressure bearing, sealing and plugging, and expanding the safe density window.
[0156] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0157] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a composite shape memory epoxy polymer, characterized in that: The preparation method comprises the following steps: S1: uniformly mixing the waterborne epoxy resin emulsion and the curing agent system A, and heating and curing to obtain a first cured product; S2: Evenly mix the waterborne epoxy resin emulsion and the curing agent system B, and heat and cure to obtain a second cured product; S3: Mixing the first solidified body and the second solidified body to obtain a composite shape memory epoxy polymer sheet, wherein the thickness of the sheet is 0.5-1 mm.
2. The preparation method according to claim 1, characterized in that: The waterborne epoxy resin includes at least one of epoxy resin E51, GEM254, epoxy resin GEM370, and polypropylene glycol diglycidyl ether PPGGE.
3. The preparation method according to claim 1 or 2, characterized in that: The curing agent system A comprises at least one of a monoamine curing agent, a polyamine curing agent, and a polyphenol compound; preferably at least one selected from diglycolamine (DGA), tetravinylpentamine-TETA, D230, D400, tannic acid, catechol, and dopamine; more preferably, the curing agent system A is a mixture of diglycolamine-DGA and tetravinylpentamine-TETA, wherein the mass ratio of diglycolamine-DGA to tetravinylpentamine-TETA is (3-8):1; The mass of the curing agent system A is 30-50% of the mass of the waterborne epoxy resin.
4. The preparation method according to any one of claims 1 to 3, characterized in that The curing agent system A also includes binary polyether epoxy, and the binary polyether epoxy is preferably polypropylene glycol diglycidyl ether. The addition amount of the binary polyether epoxy is 5-10% of the mass of the waterborne epoxy resin.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S1, the heating curing conditions include: curing temperature of 60-120°C, curing time of 2-6h; preferably, the heating curing is step-temperature curing, including curing at 60-80°C for 4h and curing at 100-120°C for 2h, wherein the glass transition temperature is 60-80°C.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The curing agent system B includes at least one of an aromatic amine curing agent and a polyamine curing agent, preferably selected from at least one of diethyltoluenediamine-DETDA, diaminodiphenyl sulfone-DDS, diaminodiphenylmethane-DDM, tetravinylpentamine-TETA, and polyetheramine D230; more preferably, the curing agent system B is a mixture of diaminodiphenyl sulfone-DDS and tetravinylpentamine-TETA; wherein the mass ratio of diaminodiphenyl sulfone-DDS to tetravinylpentamine-TETA is (1-5):1; the mass of the curing agent system B is 60-80% of the mass of the waterborne epoxy resin.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step S2, the heating and curing conditions include: heating temperature of 60-140°C, curing time of 2-12h; preferably, heating and curing is step-by-step temperature curing, including curing at 60-80°C for 3-5h, curing at 100-120°C for 1-3h, and curing at 120-140°C for 2-4h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step S3, the mass ratio of the first solidified body to the second solidified body is (1-2): 1; The mixing method of the first solidified body and the second solidified body includes hot pressing and sheeting; Wherein, the conditions for hot pressing the first solidified body and the second solidified body in a ratio of 1:1 include: temperature of 120-160°C and pressure of 8-10Mpa; The conditions for hot pressing the first solidified body and the second solidified body in a ratio of 2:1 include: a temperature of 120-160° C. and a pressure of 8-12 MPa.
9. A composite shape memory epoxy polymer obtained by the preparation method according to any one of claims 1 to 8, wherein the expansion rate is 40-70%.
10. Use of the composite shape memory epoxy polymer obtained by the preparation method according to any one of claims 1 to 8 or the composite shape memory epoxy polymer according to claim 9 in the field of plugging agents; Preferably, the composite shape memory epoxy polymer is crushed and combined with a plugging material to be used as a plugging agent for crack plugging.
Citation Information
Patent Citations
Memory polymer type temperature control rigid expansion plugging agent and preparation method thereof
CN113122204A
Shape memory leak prevention and sealing system, its preparation method and application
CN113652212B
A high-temperature shape memory foam composite material, its preparation method and its application in leak sealing.
CN114702722B
Preparation method of triple shape memory composite material
CN104893250A
Multi-section recovery shape memory structure and preparation method thereof
CN108300349A